Analysing the macrostructure of spoken strategic communication: an application of argumentation analysis on high-technology newly-public firms’ earnings conference calls - Papadopoulou, Tina; Theoharakis, Vasilis; Jones, Marian V.; Bhaumik, Sumon K. (Wiley, 2022)
A firm's ability to fulfil their strategic goals largely depends on how they communicate their strategies with stakeholders. Argumentation plays a prominent role in the process of communicating with stakeholders, with the intention of persuading them and achieving goals of strategic significance. In this respect, analysing argument structure is of particular importance, since determining the components that comprise an argument is a prerequisite for evaluating its acceptability and, consequently, its ability to persuade. Therefore, employing a framework that is specifically developed for the analysis of argument structure can help address questions that are not otherwise tractable. The relatively few available empirical studies in strategic communication employ frameworks that are not optimized for spoken communication. As such, there is scope to adapt/refine existing frameworks to facilitate meaningful analysis of spoken strategic communication. In this paper, therefore, we draw on existing frameworks and posit an adaptation that enables us to analyse the macrostructure of spoken arguments. We demonstrate the application of this adapted framework by analysing earnings conference calls involving three high-technology firms and financial analysts. By doing so, our study contributes to management practice and the literatures on strategic communication, as well as financial communications and investor relations.
Keywords: Argumentation analysis; Toulmin’s argumentation framework; strategic communication; spoken strategic communication; earnings conference calls